ARTICLE STUDY ON APPLICABILITY AND FEEDING PREFERENCES OF AQUATIC INSECTS - S. K. Verma, (International Journal of Innovations in Engineering Research and Technology, 2014)
Aquatic macroinvertebrates play an important role in a wide range of ecological processes. Primary production, detritus decomposition, nutrient mineralization, and downstream spiralling are just some of the processes they have a significant impact on. The categorization of functional feeding groups (FFGs) was created to make it easier to include macroinvertebrates in aquatic ecosystems research. When macroinvertebrates consume resources, their physical properties (such as the specialisation of mouth parts) and behavioural processes (such as feeding strategy) are combined in this categorization. In spite of recent advancements in macroinvertebrate identification, there is still a lack of knowledge on the FFG assignment. FFG classification has also undergone considerable alteration because of a focus on gut content analysis, which is more suited for assigning trophic guilds than using the FFG classification alone. These objectives are to present an overview of the usefulness of utilising the FFG classification, synthesise known information on aquatic insects in Latin America using the FFG, and provide basic instructions on how to allocate species to their FFGs in this research. The purpose of FFGs is to show the impact organisms may have on their habitats and the resources they use. Groups such as scrapers, shredders, and collectorsgatherers use modified mouth parts to sieve or collect small particles (1mm) accumulating on the stream bottom, while filterers use special adaptations to remove particles from the water directly. Other groups include filterers, which remove particles directly from the water. The piercers that drink plant juices by cutting or puncturing the tissue with their mouth parts and feed on vascular plants are also covered in depth. A list of aquatic insect families in Latin America, with an initial assignment to FFGs, is also provided in this section When allocating FFGs based on the contents of one's stomach, we advised care.